A New Global Search for the Ground State Structure of Small Cluster: Application to S6 (Journal of Atomic and Molecular Sciences, 2013)
Initial configuration plays an important role in molecular dynamics (MD)simulation. Based on ab initio MD simulation used widely, we here first introduce aglobal search method for the ground state structure of clusters. We think that duringa simulation, each type of atoms in cluster should be in equivalent sites when wechoose the initial configuration. Thus, our proposal is an improvement in eliminatingthe ``unequal" in traditional annealing technology, and the results should be more convinced.Moreover, our method can make us obtain all possible structures of clusters,and also get some new structures, which are left out by previous studies. As an illustrativeapplication, we here examine the $S_6$ cluster and found many structures (e.g. $D_{3d},$ $C_{2v},$ $D_{3h},$ $C_s$ and $C_1$). The geometrical parameters and vibrational frequencies arein agreement with experimental values.
Keywords: sulfur cluster; Langevin molecular dynamics; density functional theory.